2020
DOI: 10.1093/jpepsy/jsaa060
|View full text |Cite
|
Sign up to set email alerts
|

Internet-Delivered Acceptance and Commitment Therapy for Adolescents with Chronic Pain and Their Parents: A Nonrandomized Pilot Trial

Abstract: Background Acceptance and Commitment Therapy (ACT) is an empirically supported treatment for chronic pain in adults. There is also a small but growing evidence base of ACT for pediatric chronic pain. However, because of limited access to psychological treatment for pain, and geographical distances from pain facilities, many patients will not receive such treatment. Objective The aim of the study was to evaluate the feasibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Studies have shown an increase in the EC levels even after short-term meditation practice, providing evidence of the analgesic potential of mindbody therapies (Sadhasivam et al, 2020). Understanding and individualizing the treatment and matching it to the patient's requirement can improve treatment response, adherence, and outcomes (Day et al, 2020;Zetterqvist et al, 2020). Considering at-home practices and online modules can improve reach and compliance with mindfulness-based therapies (Day et al, 2020;Zetterqvist et al, 2020).…”
Section: Non-pharmacological Therapiesmentioning
confidence: 99%
“…Studies have shown an increase in the EC levels even after short-term meditation practice, providing evidence of the analgesic potential of mindbody therapies (Sadhasivam et al, 2020). Understanding and individualizing the treatment and matching it to the patient's requirement can improve treatment response, adherence, and outcomes (Day et al, 2020;Zetterqvist et al, 2020). Considering at-home practices and online modules can improve reach and compliance with mindfulness-based therapies (Day et al, 2020;Zetterqvist et al, 2020).…”
Section: Non-pharmacological Therapiesmentioning
confidence: 99%
“…Digital delivery of pain management treatments offers promise for expanding access to treatment beyond the context of a global pandemic. Before COVID-19, considerable research was being conducted to develop digital solutions and assess the feasibility and effectiveness of interventions for youth with chronic pain delivered via the Internet and smartphone/mobile technologies 34–38. Feasibility and effectiveness of these remotely delivered health interventions for youth with chronic pain have been demonstrated via clinical trials, with effectiveness demonstrated in real-world settings as well 39.…”
Section: Discussionmentioning
confidence: 99%
“…Before COVID-19, considerable research was being conducted to develop digital solutions and assess the feasibility and effectiveness of interventions for youth with chronic pain delivered via the Internet and smartphone/mobile technologies. [34][35][36][37][38] Feasibility and effectiveness of these remotely delivered health interventions for youth with chronic pain have been demonstrated via clinical trials, with effectiveness demonstrated in real-world settings as well. 39 Yet, there are still many future directions to be explored within the context of digital behavioral health care delivery.…”
Section: Future Directionsmentioning
confidence: 99%
“…There were short-term pain decreases with headaches, but the results did not last for more than at least three months. However, wait times for pain clinics were reported to be around 197.5 days, and virtual CBT might allow teenagers to receive psychiatric care geared toward the management of their chronic pain more quickly and at a reduced cost [ 19 ]. In an Internet-based setting, acceptance and commitment therapy has shown favored efficacy in treating child and adolescent chronic pain and following related domains, including depressive symptoms and psychological inflexibility [ 20 ].…”
Section: Discussionmentioning
confidence: 99%